Beyond the Hippocratic Oath: A Planetary Health Pledge for the Malaysian Medical Community - Jemilah, Mahmood * (Penerbit Universiti Sains Malaysia, 2022)
Today, humanity is facing a myriad of crises affecting our collective health as well as that of planet Earth, driven by a complex interplay of political, social, economic, environmental and humanitarian factors. The global SARS-CoV-2 (COVID-19) pandemic has provided unquestionable evidence of the critical relationships between health, environment and economy, and tested the resilience of societies, including in Malaysia where we encountered first-hand the effects of a compounding disaster during the torrential downpours that befell eight states in December 2021 (1), and again, through the unforeseen tornado-like freak storm or fair-weather waterspout in Ipoh (2) just days ago. The World Health Organization estimates that one out of four deaths globally result from exposure to environmental threats (3). As air quality is steadily worsening (4), Malaysians are not exempt from illnesses and deaths related to environmental threats, particularly respiratory and cardiovascular illnesses (5). These crises are glaring reminders of humanity’s long-standing violation of planetary boundaries (6) through indiscriminate and unsustainable development practices that have led to the loss of many lives, disrupted and placed phenomenal burdens on health services, fractured livelihoods and negatively affected mental health.